THE SERVICE TARGETED BY THE CSP IS FWA WITH A “FIBER-LIKE” EXPERIENCE. (INTERNATIONAL CONFERENCE ON ADVANCE SCIENCE AND TECHNOLOGY, 2025)
The wavelengths of mmWave signals are short, as are the antenna elements. Consequently, the energy density of the signal reaching the antenna must be high to get a sufficient signal-to-noise level. Using large antenna arrays on the transmitter side together with beamforming enables the energy to be focused in the desired direction. Beamforming on the receiver side further improves the received signal strength.